PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PEMADAM KEBAKARAN PADA SATUAN POLISI PAMONG PRAJA DAN PEMADAM KEBAKARAN KABUPATEN MERAUKE - Sumarwati; Syahrabudin Husein Enala; Aenal Fuad Adam (Papsel Journal of Humanities and Policy, 2025)
This study aims to analyze the effect of work discipline on the performance of employees at the Police Pamong Praja and Fire Department of Merauke Regency. Work discipline is considered one of the factors that is expected to enhance employee performance, especially in carrying out operational tasks that require punctuality and responsibility. This study uses a quantitative method with a simple linear regression approach to test the effect of work discipline (independent variable) on employee performance (dependent variable). The sample used in this study consists of 40 respondents, who are employees of the Police Pamong Praja and Fire Department of Merauke Regency. The results of the study show that the t-value for work discipline (X) is 8.479, which is greater than the t-table value of 2.026. In addition, the significance value for work discipline (X) is 0.000, which is smaller than the probability value of 0.005. Therefore, it can be concluded that H0 is rejected and H1 is accepted, meaning that there is a significant effect of work discipline on employee performance at the Police Pamong Praja and Fire Department of Merauke Regency. These findings indicate that the better the work discipline of employees, the higher the performance produced. This study provides important contributions in understanding how work discipline can play a role in improving employee performance in government institutions, particularly in the fire department sector.